Thermo Electric Generator (Future renewable energy source) - Kulshreshtha, Shubham; Singh, Satendra (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
Electricity has become a necessity for everyone. Electricity is no longer a luxury; it has become a necessity in our everyday lives. It’s very difficult to live without electricity for an extended period of time. We know that how electrical energy being generated in India by several method such as diesel, steam, Hydro etc. power plant have generated electrical energy as per requirement. But different method of generation has different merits and demerits like costly, bulky and expensive. Now a days facing fuel cost, we required the low cost, high efficient and easy to use renewable energy to the home or emergency purposes mostly when power cut occur. Advantage of Thermoelectric generators Electrical power will be user friendly, clean and fresh and increases interest in renewable energy. It can use waste heat energy produce by machinery works and other process that produce thermal energy. Here we discussed about the new ideas of electrical generation, called thermoelectric generators. Thermoelectric generators could be used in power plants in order to convert waste heat into additional electrical power and in automobiles as automotive thermoelectric generators (ATGs) to increase fuel efficiency.